2018
DOI: 10.1101/333823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aggregation ofVibrio choleraeby cationic polymers enhances quorum sensing but over-rides biofilm dissipation in response to autoinduction

Abstract: 19Vibrio cholerae is a Gram-negative bacterium found in aquatic environments and a human 20 pathogen of global significance. Its transition between host-associated and environmental life 21 styles involves the tight regulation of niche-specific phenotypes such as motility, biofilm formation 22 and virulence. V. cholerae's transition from the host to environmental dispersal usually involves 23 suppression of virulence and dispersion of biofilm communities. In contrast to this naturally 24 occurring transition, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
(45 reference statements)
2
2
0
Order By: Relevance
“…Following our previous work with V. cholerae, 31,32 for which we had seen an increase in biofilm formation upon incubation with cationic polymers, we postulate here that this polymerinduced biofilm formation can be exploited in other microorganisms for the production of biofilms for biotechnology.…”
Section: Polymer-induced Biofilm Formation: Screening Chemical Spacesupporting
confidence: 69%
See 3 more Smart Citations
“…Following our previous work with V. cholerae, 31,32 for which we had seen an increase in biofilm formation upon incubation with cationic polymers, we postulate here that this polymerinduced biofilm formation can be exploited in other microorganisms for the production of biofilms for biotechnology.…”
Section: Polymer-induced Biofilm Formation: Screening Chemical Spacesupporting
confidence: 69%
“…4,[23][24][25][26] In our case, we focused on biocatalysis, where biofilms can protect microbial cells from harsh conditions such as extreme pH or temperature, or from the presence of detrimental chemicals such as organic solvents. In our previous work, we had exploited cationic polymers to induce clustering in a range of bacteria, including Vibrio harveyi, [33][34][35][36] V. cholerae, 31,32 Pseudomonas aeruginosa, 34,35 Staphylococcus aureus 35 and E. coli, 34,35 and, as just mentioned, we observed increased biofilm formation for V. cholerae. However, we also observed that cationic polymers were toxic to some of the E. coli strains employed.…”
Section: Polymer-induced Biofilm Formation: Screening Chemical Spacesupporting
confidence: 55%
See 2 more Smart Citations